Creative resources for the early childhood classroom - Herr, Judy. (Unites States of America : Wadsworth Cengage Learning, 2013)
A theme based curriculum, this book is presented in Alpha order and contains over 2500 new activities, books, and songs; five new multicultural themes, new green themes, and various sections have been updated. Themes range from Ants to Zoo animals. Each theme contains a variation of the following content depending upon that theme: Curriculum, web, theme goals, concepts for the children to learn, vocabulary, bulletin board, parent letter, music, fingerplay, science, math, dramatic play, arts and crafts, sensory, large muscle (gross), small muscle (fine), field trips, social studies, group time, cooking, transitions, books, multimedia, recordings and song titles.
1. Ants -- 2. Apples -- 3. Art -- 4. Birds -- 5. Blue -- 6. Bread -- 7. Brushes -- 8. Bubbles -- 9. Buildings -- 10. Camping -- 11. Caring for Our Earth -- 12. Cars, Trucks and Buses -- 13. Cats -- 14. Chinese New Year -- 15. Christmas ...
Keywords: UNIT METHOD OF TEACHING